Estudo de osmotinas e taumatinas vegetais para a prospecção de peptídeos antimicrobianos - Lopes, Francisco Eilton Sousa (2018)
Osmotin- and thaumatin-like proteins (OLPs and TLPs) have been related to plant defense because they are induced in response to different biotic and abiotic stresses. In the present work, several OLPs and TLPs were prospected to the identification of antimicrobial peptides by bioinformatic analyses, which were further synthesized, characterized, and their activities and action mechanisms assayed against some phytopathogenic fungi, bacteria and yeasts. Four peptides were selected considering some chemical parameters (GDCKATSC, CPRALKVPGGCN, IVGQCPAKLKA, and CAADIVGQCPAKLK). Antimicrobial assays showed that the peptides were not able to inhibit the mycelia growth of phytopathogenic fungi as well as they did not affect the bacterial cell growth. Significant biological activity was found only for two peptides (CPRALKVPGGCN and CAADIVGQCPAKLK) against Candida albicans and Saccharomyces cerevisiae. Fluorescence and scanning electron microscopy assays demonstrated the peptide CAADIVGQCPAKLK did not alter yeast membrane integrity. However, it was able to induce the production of reactive oxygen species and apoptosis. Molecular docking analysis showed that the peptide CAADIVGQCPAKLK interacted with a very low binding affinity energy with a specific plasma membrane receptor of C. albicans and S. cerevisiae, which have been described to promote the induction of apoptosis. The results indicate that peptide CAADIVGQCPAKLK can be a good candidate for the development of a specific antimicrobial agent against the pathogen C. albicans.